Relationships Between Northern Hemisphere Teleconnection Patterns and Phytoplankton Productivity in the Neva Estuary (Northeastern Baltic Sea) - Golubkov, Mikhail; Golubkov, Sergey (Frontiers in Marine Science, 2021)
Teleconnection patterns can be an important tool for investigating the impact of climate change on biological communities. The aim of the study was to use 2003‒2020 data on chlorophyll a concentrations (CHL) and plankton primary production (PP) in midsummer to determine which of the teleconnection patterns have most pronounced effects on phytoplankton productivity in the estuary located on the border between western and eastern Europe. CHL correlated significantly with the winter values of the North Atlantic Oscillation (NAOw) and Scandinavia (SCANDw) indices, as well as with the values of the annual Polar/Eurasian (POLy) and annual Arctic Oscillation (AOy) indices. PP was significantly correlated with the values of POLy. East Atlantic/Western Russia pattern showed no significant correlation with both phytoplankton indicators. Stepwise multiple linear regressions were performed to determine the most influential indexes affecting CHL and PP in the Neva Estuary. POLy, SCANDw and NAOw appeared to be the main predictors in CHL multiple regression model, while the values of POLy and the July NAO and SCAND values were the main predictors in the PP model. According to our research, the productivity of phytoplankton in the Neva Estuary, located in the most northeastern part of the Baltic Sea, showed a significant relationship with the POL, which determines weather conditions in the northeastern regions of Eurasia. Possible mechanisms of the influence of these teleconnection patterns on phytoplankton productivity are discussed. Using the obtained multi-regression equations and the values of climatic indices, we calculated the values of CHL and PP for 1951‒2002 and compared them with the results of field observations. The calculated and measured values of CHL and PP showed a significant increase in phytoplankton productivity in the Neva Estuary in the second half of the 2010s compared to earlier periods. In some years of the 1950s, 1980s and late 1990s, CHL could also be above average and the low phytoplankton productivity should have been observed in the 1960‒1970s. This indicates a significant contribution of current climate change to fluctuation in phytoplankton productivity observed in recent decades, which should be taken into account when developing measures to protect aquatic ecosystems from eutrophication.